2007
DOI: 10.1104/pp.107.109934
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Purple Acid Phosphatase with Phytase Activity Increases Foliar Ascorbate

Abstract: Ascorbate (AsA) is the most abundant antioxidant in plant cells and a cofactor for a large number of key enzymes. However, the mechanism of how AsA levels are regulated in plant cells remains unknown. The Arabidopsis (Arabidopsis thaliana) activationtagged mutant AT23040 showed a pleiotropic phenotype, including ozone resistance, rapid growth, and leaves containing higher AsA than wild-type plants. The phenotype was caused by activation of a purple acid phosphatase (PAP) gene, AtPAP15, which contains a dinucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
121
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 67 publications
4
121
0
1
Order By: Relevance
“…The biochemical properties of the recombinant AtPAP15 from plant were very different from that presented by Zhang et al (2008), who reported the specific activities of a GST:AtPAP15 toward a few substrates. In our study, the GST:AtPAP15 produced from E. coli was inactive.…”
Section: Kinetic Parameters Of Purified Atpap15mentioning
confidence: 43%
See 2 more Smart Citations
“…The biochemical properties of the recombinant AtPAP15 from plant were very different from that presented by Zhang et al (2008), who reported the specific activities of a GST:AtPAP15 toward a few substrates. In our study, the GST:AtPAP15 produced from E. coli was inactive.…”
Section: Kinetic Parameters Of Purified Atpap15mentioning
confidence: 43%
“…In our study, the GST:AtPAP15 produced from E. coli was inactive. Zhang et al (2008) reported the specific activity of GST:AtPAP15 toward pNPP to be only 0.546 units mg 21 , which was far lower than the plant-derived AtPAP15 level (165 units mg 21 ; Table III) and that reported for the other plant PAPs (222-368 units mg 21 for tomato [Solanum lycopersicum] PAPs [Bozzo et al, 2002] and 266 units mg 21 for KbPAP [Vogel et al, 2002]). Regarding specific activities toward phytate, the two recombinant AtPAPs gave 10.0 (plant) and 0.7 (bacterial) units mg 21 , respectively.…”
Section: Kinetic Parameters Of Purified Atpap15mentioning
confidence: 90%
See 1 more Smart Citation
“…Overexpression of AtPAP15 in Arabidopsis significantly decreased phytate content in leaves (Zhang et al, 2008). Sequence analysis indicates that AtPAP15 exhibits 74% similarity to the soybean (Glycine max) phytase gene, GmPhy (Hegeman and Grabau, 2001).…”
mentioning
confidence: 99%
“…AtPAP15, a purple APase with confirmed phytase activity from Arabidopsis, can hydrolyze myoinositol hexakisphosphate, yielding myoinositol and Pi (Zhang et al, 2008). Overexpression of AtPAP15 in Arabidopsis significantly decreased phytate content in leaves (Zhang et al, 2008).…”
mentioning
confidence: 99%